Semiconductor Detector Study for Detecting Fusion Neutrons using Geant4 Simulations - Kaperoni, Kalliopi; Diakaki, Maria; Kokkoris, Michael; Axiotis, Michael; Ziagkova, Anastasia; Weiss, Christina; Vlastou, Roza (HNPS Advances in Nuclear Physics, 2023)
Accurate neutron flux measurements in fusion reactors are essential, in order to determine the feasibility and progress of the reaction as well as for safety issues. Semiconductor neutron detectors exhibit promising characteristics for operation in the extreme environmental conditions of fusion reactors. Silicon, Diamond and Silicon Carbide are the most studied and anticipated materials for constructing detectors with high efficiency and irradiation resistance. The ITER fusion reactor is expected to run D-D plasma measurements in the near future, so the detection of 2.45 MeV neutrons with appropriate detectors is of great and immediate importance. In the present work the study of 2.45 MeV neutrons interactions with a silicon, diamond and silicon carbide detector was made, using GEANT4 [1] simulations, in order to compare their response. An experimental study will follow at the neutron production facility of the TANDEM accelerator of the I.N.P.P. of the NCSR “Demokritos”, with detectors provided by CIVIDEC Instrumentation GmbH, so the geometry of the simulations was built accordingly. A quasi-monoenergetic neutron beam of 2.45 MeV was produced through 3H(p,n) reactions in a TiT target. Due to the low cross section of the reaction, biasing techniques were implemented in the simulation to increase the counting rate and thus producing realistic results. These biasing techniques were studied, with various tests and the parameters affecting the choice of the biasing factor are shown and discussed.